The suitability of telecommunication (wired and wireless) systems in the practice of democracy and human rights in Iraq (Texas Journal of Engineering and Technology, 2022)
The 21st century is characterized by different trends, including advanced digital technologiesand services. These technologies comprise advanced telecommunication systems that enhancecommunication between different parties thus, ease of information awareness between people in differentlocations. For this reason, telecommunication systems have been used by government agencies and NGOsto help promote the practice of democracy and respect for human rights. Countries such as Iraq have beenidentified as entities that use telecommunication systems to positively and negatively encourage thepractice of human rights and democracy. This study aims to discuss the suitability of telecommunicationsystems in the practice of democracy and human rights in Iraq. The paper has used the case study datacollection method to acquire an in-depth and multi-faceted understanding of the complex issue in its reallifecontext. The results show that telecommunications have been used often to ensure democracy andhuman rights are effectively practised. The paper's results comprise 4 case studies that show the positiveuse of telecommunication systems in the practice of human rights and democracy within a given country.In contrast, two case studies show examples of negative use of telecommunication systems based onretaining control or governmental power. Lastly, one case study shows how telecommunication systemscan be important in regions where governance, democracy and human rights are not intact. The study'sfindings show that telecommunication systems benefit governments and citizens by ensuring thatdemocracy and human rights are practised appropriately.